2020
DOI: 10.33735/phimisci.2020.i.39
|View full text |Cite
|
Sign up to set email alerts
|

Dissolving the self

Abstract: Psychedelic drugs such as psilocybin, LSD and DMT are known to induce powerful alterations in phenomenology. Perhaps of most philosophical and scientific interest is their capacity to disrupt and even “dissolve” one of the most primary features of normal experience: that of being a self. Such “peak” or “mystical” experiences are of increasing interest for their potentially transformative therapeutic value. While empirical research is underway, a theoretical conception of the mechanisms underpinning these exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 115 publications
0
28
0
Order By: Relevance
“…The experiential feeling of being a "witnessing observer" (self in the act of knowing) can be voluntary manipulated (enhanced and sharpened), for example, as a function of meditation training (Fingelkurts et al, 2016b,c;Lutz et al, 2008;Kerr et al, 2011), or arise in pathologic circumstances like depression (Fingelkurts & Fingelkurts, 2017a), and post-traumatic stress disorder (Fingelkurts & Fingelkurts, 2018). It can also diminish or disappear, as for example, in patients with disorders of consciousness (Fingelkurts et al, 2012(Fingelkurts et al, , 2016aFingelkurts & Fingelkurts, 2017b, Huang et al, 2014, during dreamless sleep (Thompson, 2015;Windt, 2015), in specific meditative states (Wahbeh et al, 2018;Josipovic, 2019) or under psychedelics like 5-MeO-DMT (Millière, 2017(Millière, , 2020Deane, 2020;Letheby, 2020).…”
Section: The Triad Model Of the Complex Experiential Selfhoodmentioning
confidence: 99%
“…The experiential feeling of being a "witnessing observer" (self in the act of knowing) can be voluntary manipulated (enhanced and sharpened), for example, as a function of meditation training (Fingelkurts et al, 2016b,c;Lutz et al, 2008;Kerr et al, 2011), or arise in pathologic circumstances like depression (Fingelkurts & Fingelkurts, 2017a), and post-traumatic stress disorder (Fingelkurts & Fingelkurts, 2018). It can also diminish or disappear, as for example, in patients with disorders of consciousness (Fingelkurts et al, 2012(Fingelkurts et al, , 2016aFingelkurts & Fingelkurts, 2017b, Huang et al, 2014, during dreamless sleep (Thompson, 2015;Windt, 2015), in specific meditative states (Wahbeh et al, 2018;Josipovic, 2019) or under psychedelics like 5-MeO-DMT (Millière, 2017(Millière, , 2020Deane, 2020;Letheby, 2020).…”
Section: The Triad Model Of the Complex Experiential Selfhoodmentioning
confidence: 99%
“…First, like all other aspects of cognition and experience the self must also be a construction built out of hierarchical models driven by past experience. Indeed, according to Friston (2018) and others (e.g., Deane, 2020) possessing a self-model is a natural consequence of active inference and prospection: One cannot predict future actions without representing oneself in those actions. For example, picking up a glass of water requires that we have a model of our body as an intentional agent who can pick up a glass of water given certain behaviors.…”
Section: The Inferred Hierarchical Selfmentioning
confidence: 99%
“…We have suggested that the reason these changes in self experience occur in meditation is through a gradual reduction in temporally deep processing by resting awareness to the here and now. On the other hand, following the REBUS model, changes in self-processing purportedly occur due to the entropic effects of psychedelics on existing priors (which may also 'flatten' or 'collapse' the hierarchy, Girn et al, 2020;Deane, 2020), and thus ordinary self-modelling breaks down. Thus, we propose that meditation gradually abates the emergence of generative models by restricting awareness to the here and now, whereas psychedelics loosens priors and, in this way, leads to the dissolution or "mergence" of self-world boundaries in experience.…”
Section: Dissolving or Disappearing: Psychedelics And Meditationmentioning
confidence: 99%
“…What supports Saks's description, however, is that other reports converge on similar themes, for example reports of psychedelic experiences (see especially Letheby & Gerrans, 2017;Millière, 2017; see also Deane, 2020, this issue, as well as Letheby, 2020, this issue): I realized then that I wasnt [sic] myself, I wasn't anything anymore. I had been broken down into nothingness, into oblivion.…”
mentioning
confidence: 72%